2005
DOI: 10.1300/j017v23n03_09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Traditional and Web-Assisted Instruction in an Undergraduate Social Work Practice Class

Abstract: This article addresses the dearth of research utilizing a quasi-experimental design and student performance measures in assessing web-assisted instruction in social work undergraduate practice courses. Social work students were randomly placed into two sections of a practice course. The experimental section (n = 18) students received 50% of course lectures with web-assisted instruction while the compari-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Students in both sections reported statistically more favorable attitudes toward lesbians and gay men. Petracchi, Mallinger, Engel, Rishel, and Washburn (2005) studied the comparative effectiveness of traditional and Web-assisted modalities in an undergraduate practice class. The traditional section involved face-to-face lectures, discussion, and role-play activities.…”
Section: Research Literature: New Versus Old Teaching Technologiesmentioning
confidence: 99%
“…Students in both sections reported statistically more favorable attitudes toward lesbians and gay men. Petracchi, Mallinger, Engel, Rishel, and Washburn (2005) studied the comparative effectiveness of traditional and Web-assisted modalities in an undergraduate practice class. The traditional section involved face-to-face lectures, discussion, and role-play activities.…”
Section: Research Literature: New Versus Old Teaching Technologiesmentioning
confidence: 99%
“…The sample size, particularly of the on-campus MSW students, was small. Despite this limitation, the sample represents a diverse set of students including BSW, MSW, and off-campus students and appears to exceed sample sizes of similar CAI studies in social work education (Ouellette et al, 2006;Petracchi et al, 2005). Social desirability is another possible limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in Siebert et al (2006), 25 MSW students enrolled in an online practice elective reported a significant increase in clinical skills compared to the 78 students enrolled in a traditional section of a practice course. Others have reported no significant difference between traditional and technological pedagogy (Ouellette et al, 2006;Petracchi et al, 2005).…”
Section: Computer-assisted Social Work Instructionmentioning
confidence: 98%
See 1 more Smart Citation
“…The literature is replete with rationales for selecting either online or in-class course methods for social work course delivery. On the one hand, off campus online education is viewed as an ideal mechanism for increasing the accessibility of social work programs (Alonso, López, Manrique, & Viñes, 2005;Brand, 1995;Petracchi, Mallinger, Engel, Rishel, & Washburn, 2005), which is in keeping with the social work values of inclusion and empowerment. There is evidence that "students now more than ever before are juggling multiple responsibilities of study, working in paid employment and providing child and/or parental care" (McInnis, James, & Hartley, 2000, as cited in Maidment, 2005, p. 186).…”
Section: Literature Reviewmentioning
confidence: 99%